(3CWdS JGQjN GdOhdI GdCehjI (B/s - (3GdeZdhK, SGej YHO Gddg,s 1382 (3gLQj(B-s ((3GdQjGV(B:s (3ecJHI GdYHjcGf,s, 2011)
(3jJfGhd gPG GdcJGH GdehShe H` (B( (3CWdS JGQjN GdOhdI GdCehjI (B) (3bjGe GdOhdI GdCehjI Ydi jO CejQ GdeDefjf eYGhjI Hf CHj Sa`jGf(B-(3QVj Gddg YfgeG(B-(3a`j hbJ cGf GdeSdehf CMhL eG jchfhf a`jg Edi hMOI GdUa, hLeY GdcdeI, hQCH GdUOY, hdG SjeG HYO JfGRd GdMSf Hf Ydj(B-(3QVj Gddg YfgeG(B-(3HGdNdGaI GdGehjI a`j (B"(3YGe GdLeGYI(B" (3YGe (B41 (3g`(B/ 661 (3e(B. (3hefP Pdc GdMjf hGdOhdI GdCehjI JMed Ydi YGJbgG fTQ dhGA GdESdGe a`j CUbGY GdeYehQI(B. (3MjK CQSi eYGhjI cjGfgG cNdGaI bhjI, LPH eNGda`jg Ydi WGYJg, hYed Ydi JhMjO cdeI GdeSdejf(B. (3hJejR Mceg HGdMceI hGdYOd (B((3Cehj ddYdG QMdJg hGdeYGdj HeWj hWQb(B)(3, hhUd ETYGY GdMVGQI GdESdGejI ef OeTb Edi CUbGY HYjOI ef GdYGde, dJchf GdOhdI GdCehjI CcHQ OhdI ESdGejI YQagG GdJGQjN, Ke JhGdi GdNdaGA ef Hfj CejI GdMce ef HYOg(B. (3hgPG GdCWdS jbhe HJhXja gPG GdLgO GdYXje YHQ NQGFW JaUjdjI, hUhQ eYHQI, hfUhU eNJGQI, djchf eQBI eYHQI Yf gPg GdaJQI GdJGQjNjI GdegeI ef JGQjN GdCeI GdESdGejI(B.s
Keywords: (3JGQjNs -- (3GdOhdI GdCehjIs -- (3CWGdSs